Comportamento hidrodinâmico de quebra-mares flutuantes - Pedrosa Junior, Oswaldo Antunes (1980)
Present two-dimensional mathematical model to study the performance of a rigid floating break water with uniform geometry and operating under regular wave conditions. To solve the hydrodynamic problem one distributes sources on the body contour and then formulates an integral equation which is solved numerically. Our goal is to obtain the most important parameters in the analysis of a wavebreaker, that are the transmission coefficient, the hydrodynamic loads and the motions of the body. The numerical results for the transmission coefficient and the motions of a body with retangular cross section were compared with available test data and they showed a good agreement. The numerical results for a catamaran cross section and the irregular frequency phenomenum are presented too.